2011
DOI: 10.1097/nmd.0b013e31822142ac
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Sexual Abuse Severity and Disclosure as Predictors of Depression Among Adult African-American and Latina Women

Abstract: A history of childhood sexual abuse (CSA) has been associated with adult depression, but data on abuse severity and disclosure are scant, particularly among low income ethnic minorities. CSA often co-occurs with other adversities, which also increase the risk of depression. This study examined the peri-trauma variable of abuse severity and the post-trauma variables of disclosure and self-blame as predictors of current depression symptoms in 94 low-income African American and Latina women with histories of CSA.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
30
0
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 79 publications
(90 reference statements)
3
30
0
6
Order By: Relevance
“…These patterns are largely consistent with previous studies showing links between CSA severity and clinically meaningful PTSD or depression symptoms 38,39,74,78 and links between clinically meaningful symptoms and biomarker composite scores among women 65,67,69,74 ; they are also consistent with the links between CSA severity and clinical symptom severity reported in the baseline-only analyses of the larger sample of 99 men that included our participants. 40 Nonetheless, replication of this study is needed with a larger sample to increase the probability of effective randomization and provide adequate statistical power to further examine the effectiveness of ES-HIM in improving sexual and mental health outcomes and biomarker composites.…”
supporting
confidence: 80%
“…These patterns are largely consistent with previous studies showing links between CSA severity and clinically meaningful PTSD or depression symptoms 38,39,74,78 and links between clinically meaningful symptoms and biomarker composite scores among women 65,67,69,74 ; they are also consistent with the links between CSA severity and clinical symptom severity reported in the baseline-only analyses of the larger sample of 99 men that included our participants. 40 Nonetheless, replication of this study is needed with a larger sample to increase the probability of effective randomization and provide adequate statistical power to further examine the effectiveness of ES-HIM in improving sexual and mental health outcomes and biomarker composites.…”
supporting
confidence: 80%
“…One of the most commonly reported predictors of prenatal depression is history of depression (Kapetanovic et al, 2009;Lancaster et al, 2010;Pereira, Lovisi, Pilowsky, Lima, & Legay, 2009). In addition, though not assessed specifically among pregnant women, childhood sexual abuse (CSA) has been associated with depression in women (Delany-Brumsey, Joseph, Myers, Ullman, & Wyatt, 2013;Sciolla et al, 2011). Because CSA is more prevalent among women with HIV (Koenig, Doll, O'Leary, & Pequegnat, 2004), the assessment of CSA as a correlate of depression within this population is warranted.…”
Section: Introductionmentioning
confidence: 99%
“…In some studies, disclosure has adversely affected the survivor’s psychological health, with higher levels of depression reported among those who disclosed (Lee & Kim, 2011; Sciolla et al, 2011). Additionally, the disclosure recipient may not be empowered to respond: research has shown that adolescents may be more likely to disclose to peers (Priebe & Svedin, 2008).…”
Section: Introductionmentioning
confidence: 99%